التعليم المتمايز وأثره في التحصيل الدراسي لذوي صعوبات التعلم - بقدور بن عطية, حليمة (كلية الأدب العربي والفنون, 2024)
تناولت الدراسة موضوع" التعليم المتمايز وأثره في التحصيل الدراسي لذوي صعوبات التعلم" باعتباره منهجًا تربويًا يهدف إلى تلبية احتياجات جميع المتعلمين داخل الصف الدراسي من خلال تنويع طرق التدريس والمحتوى والأنشطة بما يتناسب مع اختلاف قدراتهم ومستوياتهم التعليمية. تطرقت الدراسة إلى عدة محاور، منها التعليم المتمايز والعملية التعليمية، صعوبات التعلم، والتعليم المتمايز والتحصيل الدراسي اعتمدنا فيه على تحليل الاستبيان المستند إلى إجابات معلمي المرحلة الابتدائية. ومن خلال هذا البحث، توصلنا إلى أن التعليم المتمايز يعزز التحصيل الدراسي لذوي الصعوبات التعلمية من خلال تقديم دعم فردي ملائم يزيد من دافعيتهم ومشاركتهم، ويقلل الفجوة التعليمية بينهم وبين أقرانهم. The study addressed the topic of "Differentiated Instruction and Its Impact on Academic Achievement for Students with Learning Disabilities," considering it as an educational approach aimed at meeting the needs of all learners within the classroom by varying teaching methods, content, and activities to suit their diverse abilities and educational levels. The study covered several aspects, including differentiated instruction and the educational process, learning disabilities, and differentiated instruction and academic achievement. Our analysis relied on a survey based on the responses of primary school teachers. Through this research, we concluded that differentiated instruction enhances the academic achievement of students with learning disabilities by providing appropriate individual support, increasing their motivation and participation, and reducing the educational gap between them and their peers.
المرحلة الابتدائية أنموذجا
Keywords: التعليم المتمايز، صعوبات التعلم، التحصيل الدراسي، المرحلة الابتدائية.; Differentiated instruction, learning disabilities, academic achievement, primary education